Costly Information Acquisition - Matthew O. Jackson; James Peck (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
We examine price formation in a simple static model with asymmetric information, a countable number of risk neutral traders and without noise traders. Prices can exhibit excess volatility (the variance of prices exceeds the variance of dividends), even in such a simple model. More generally, we show that for an open set of parameter values no equilibrium has prices which turn out to equal the value of dividends state by state, while for another open set of parameter values there exist equilibria such that equilibrium prices equal the value of dividends state by state. When information collection is endogenous and costly, expected prices exhibit a "V-shape" as a function of the cost of information: They are maximized when information is either costless so that everyone acquires it, or else is so costly that no one chooses to acquire it. Prices are depressed if information is cheap enough so that some agents become informed, while others do not. If the model is altered so that information is useful in making productive decisions, then the V-shape is altered, reducing the attractiveness of prohibitively high costs.
Keywords: 330